Routing in trucking service network design problem with transsipments and driver regulations - Özgürbüz, Ekin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Most of the large transportation companies are currently trying to have the scale to operate their middle-mile or long-distance transportation plans, while using both their resources and outsourced vehicles. The aim is to deliver customer shipments from stocking origins to last-mile delivery transfer stations. Freight transportation planning is done manually in most logistics companies, often leading to poor transportation plans or plans whose quality is hard to assess. Furthermore, since transportation plans are needed almost every day, it is crucial to have a solution procedure that is as effi cient as possible. We have tried to model this environment without loss of generality while developing a methodology to solve this problem efficiently. This is an operational problem that falls into the domain of trucking service network design and operation. We offer a mathematical model and a solution methodology for this problem taking consolidation, transshipment, synchronization, and driver regulations into considera tion. Our model employs a pre-processing strategy for creating the data representing the transportation environment. Moreover, a matheuristic is presented for considering multiple periods of operation. The proposed models can be used for companies oper ating both with their own and rental vehicles. Distribution of the vehicles throughout the transportation network is crucial for the companies that operate with their own vehicles, since the aim is to plan over a horizon, rather than a single day. The assump tions and the parameters used in the models are based on data coming from already operating large companies. The benefit of using this mathematical model is to achieve a better transportation plan with a reasonable amount of time.
Keywords: Transportation -- Computer simulation.; Motor vehicle driving -- Safety regulations.